Penerapan Alat Permainan Edukatif Bertemakan Keselamatan Lalulintas Untuk Guru TK Karya Bunda Kec.Bandar Seikijang - Alfian Saleh; Muthia Anggraini; Sean Marta Efastri (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2020)
Kindergarten located in Bandar Seikijang District which is on the edge of the eastern causeway which is an accident-prone road. In addition, there is no curriculum related to traffic safety in the learning process. In overcoming partner problems, the service team provides solutions to partners in the form of assistance in making traffic safety educational tools that are applied to the curriculum in schools. The purpose of this activity is to improve the ability of teachers in making traffic safety props so that later the teachers can apply them to kindergarten students in their schools. There are four steps for implementing (1) the preparation stage, (2) the activity stage, (3) the simulation stage, (4) the evaluation stage. From the results obtained, 100% of teachers understand the importance of safety for their students. This activity provides benefits to hone the skills of teachers in the teaching and learning process by applying this educational game tool